The Historicity of Islamic Education: Tracing the Traces of Al-Irsyad and Jami'at Khair - Setyaningsih, Ari; Ulum, Davinatul; Rostanti, Nia; Purnomo, Sutrimo (Dirasah International Journal of Islamic Studies, 2024)
The research aims to trace the historicity of Islamic education at Al-irsyad and Jami'at Khair up to the present, while the research method used is library research through an in-depth analysis of the history and educational systems of the two institutions. By presenting the expected results, this research aims to understand better the effectiveness of the educational methods applied. These results may include assessing students' understanding of Islamic history and educational material Al-irsyad and Jamiat Khair. Therefore, this summary provides a comprehensive view of the contribution of research to innovation and improving the quality of Islamic education in Al Irsyad and Jami'atul Khair. By developing new organizational patterns, the Al Irsyad and Jamiat Khair movements are trying to answer the challenges and demands of modern education and da'wah in the era of globalization. The Al Irsyad organization guides the carrying out of the mandate of educational institutions under their guidance, including the formulation of educational foundations, educational insights, and reference school models in Islamic education.